Pengaruh Penggunaan Media Pembelajaran Baamboozle Pada Mata Pelajaran Sejarah Terhadap Hasil Belajar Siswa Kelas XII di SMA Negeri 5 Madiun - Putri, Vicky Diliana Sagita; Hartono, Yudi; Nurkholipah, Siti (LPPM Universitas Putera Batam, 2024)
In the era of sophisticated development, the development of science and technology has accelerated. The development of science and technology in the 21st century has influenced the entire order of life globally. In the 21st century there is a paradigm shift or way of thinking in dealing with various phenomena including mindsets related to education. The learning process in education in the 21st century requires learning strategies that are suitable for today's students. This study aims to determine the effect of using bamboozle learning media in history subjects on the learning outcomes of 12th grade students at SMA Negeri 5 Madiun. This research uses a qualitative descriptive method. The results of the study of the effect of the use of bamboozle learning media on 12th grade history subjects at SMA Negeri 5 Madiun show that: (1) The use of Baamboozle is proven to improve student learning outcomes. Students involved in learning using this media showed a significant increase in test scores. (2) The use of Baamboozle learning media in teaching History at SMA Negeri 5 Madiun has brought positive changes in the learning process and student learning outcomes. The use of this media not only improves students' understanding of the material, but also increases students' engagement in learning history. Baamboozle in History subject in class XII SMA Negeri 5 Madiun has proven to have a positive influence on students' learning outcomes. This media not only makes the learning process more interactive and fun, but also helps improve students' understanding of the material presented. With its interactive quiz feature, Baamboozle managed to change History learning from monotonous to more dynamic, thus significantly increasing student engagement.